Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/60
|View full text |Cite
|
Sign up to set email alerts
|

Preference Orders on Families of Sets - When Can Impossibility Results Be Avoided?

Abstract: Lifting a preference order on elements of some universe to a preference order on subsets of this universe is often guided by postulated properties the lifted order should have. Well-known impossibility results pose severe limits on when such liftings exist if all non-empty subsets of the universe are to be ordered. The extent to which these negative results carry over to other families of sets is not known. In this paper, we consider families of sets that induce connected subgraphs in graphs. For such families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, families of sets must have some internal structure to be succinctly represented. This internal structure may decrease the complexity of the problem, as is the case for the domain restrictions considered by Maly, Truszczyński, and Woltran (2018). We show -for a specific succinct representation that is well studied in the literature -that succinct representation can lead to a massive blow up in complexity.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…On the other hand, families of sets must have some internal structure to be succinctly represented. This internal structure may decrease the complexity of the problem, as is the case for the domain restrictions considered by Maly, Truszczyński, and Woltran (2018). We show -for a specific succinct representation that is well studied in the literature -that succinct representation can lead to a massive blow up in complexity.…”
Section: Introductionmentioning
confidence: 77%
“…Our results show that this can lead to a rise in complexity that may make recognizing strongly orderable families intractable even in applications that are not time-critical. On the other hand, Maly, Truszczyński, and Woltran (2018) showed that less expressive succinct representations can avoid this problem. Unfortunately, the representation considered in their paper is very limiting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations